The Perspectives in Gait Recognition - Kowalski, Piotr M. (Wydawnictwo Politechniki Łódzkiej, 2018)
In this paper we provide a detailed information on classical and recent research results in gait recognition. We provide classiﬁcation of leading concepts, representations, experiments and available datasets. The most promising algorithms are provided with more details and in the end we provide some predictions on future research. Paper contains also summary on methods used in a variety of papers on gait recognition published after 2002.
Keywords: gait recognition; baseline algorithm; gait energy image; biometry; gait biometry; rozpoznawanie chodu; algorytm podstawowy; obraz energii chodu; biometria; biometria chodu